A New Genuine Buckwheat Noodle Product and Its Processing from Extruded Buckweal Flour - FUKAI, Yoichi; NAKAMURA, Masako; MATSUHASHI, Tetsujiro; ISHIZAWA, Hiroaki; TAKEUCHI, Masahiko; HANAZAWA, Koichi; MATSUZAWA, Tsunetomo (NIPPON SHOKUHIN KOGYO GAKKAISHI, 1992)
Buckwheat flour treated with a twin screw extruder (EX-BW flour) was found to have a strong self dough-binding property with water. The EX-BW flours processed at the maximum extruding pressure obtained at around 130°C were very preferable to dried buckwheat noodle processing when formulated with an appropriate amount of common buckwheat flour. The optimum water absorption of the EX-BW flour was 11/2 times larger than that of common BW flour. Its dough showed a characteristic rubber-like elastic properties. A mechanical noodle processing with a simple formulation of the EX-BW flour and common BW flour at the ratio of (4:6) to (5:5) and 35% added water to the total flours was successfully carried out to prepare fine dried buckwheat noodles, a type of new genuine product, in a continuous 200kg flour processing scale. The optimum cooking time of the dried buckwheat noodles in ten times amount of boiling water was 5min. The organoleptical qualities in taste and texture were investigated.